3T Double Inversion Recovery Magnetic Resonance Imaging: diagnostic advantages in the evaluation of cortical development anomalies. Issue 5 (May 2016) - Granata, Francesca; Morabito, Rosa; Mormina, Enricomaria; Alafaci, Concetta; Marino, Silvia; Laganà, Angela; Vinci, Sergio Lucio; Briguglio, Marilena; Calamuneri, Alessandro; Gaeta, Michele; Salpietro, Vincenzo; Longo, Marcello
Abstract: Purpose: The aim of this work was to investigate the diagnostic value of the DIR sequence at 3T MR imaging operating in the evaluation of cortical development anomalies. Methods: We studied 40 patients, with a previous diagnosis of cortical dysplasia, by FLAIR-3D, DIR, FSE T2 and MPR-GE T1 sequences at 3T MRI. Two independent observers evaluated, for each sequence and lesion, some semiological aspects (cortical thickness, cortical signal intensity, white-gray matter blurring, subcortical white matter intensity). We made also a quantitative evaluation of the cortical signal intensity in lesion site, drawing a ROI on each MRI sequences and comparing them to the correspondent normal contralateral cortical area. Results: We identified 44 cortical development anomalies. Qualitative analyses showed a high level of agreement between the observers concerning DIR potentialities in detecting and characterizing the cortical development disorders. Particularly DIR sequence was able to demonstrate the blurring and the subcortical white matter anomalies. The quantitative analyses didn't show a significant difference between DIR and traditional sequences in the evaluation of the cortical signal intensity. Conclusion: 3T MRI-DIR sequence is a useful and better suitable sequence compared to the traditional sequences in the characterization of some semiological aspects of the cortical development disorders, particularly blurring and subcortical white matter hyperintensity.